Effect of atorvastatin and rosuvastatin on glucose intolerance in low dose streptozotocin induced hyperglycemic Albino rats - Gari, Manju; Kumar, Abhishek; Majhee, Lakhan (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Dyslipidemia and glucose intolerance are closely associated with each other especially as a part of metabolic syndrome. Statins are the drug of choice for treatment of dyslipidemia and for primary prevention of coronary heart disease in diabetics. Recent studies indicate risk of new onset diabetes in patients receiving statins. Hence it was worthwhile to study the effect of two most commonly used statins, which differ in their lipophilicity, on glucose tolerance in prediabetic animal model. Methods: The study consisted of 3 groups with 6 wistar rats in each and hyperglycemia was induced by intraperitoneal injection of low dose (25mg/kg) streptozotocin. Group 1 served as control, group 2 and 3 were given Atorvastatin and Rosuvastatin respectively for 8 weeks. Oral glucose tolerance test (OGTT) was performed at 0,1 and 2 hrs after glucose load on days 0, 14, 28, 42 and 56 days. Results: Starting from 28th day onwards both the treatment groups showed progressive worsening of glucose tolerance throughout the study period in comparison to the control. The impairing effect on glucose tolerance was less pronounced in Rosuvastatin group as compared to Atorvastatin. Conclusions: Hydrophilic Rosuvastatin showing less impairing effect on glucose tolerance can be a rational choice than lipophilic Atorvastatin for prevention and control of dyslipidemia in patients at risk of developing frank diabetes or having impaired glucose tolerance.